Vacation Under the Volcano : Magic Tree House #13 - Osborne, Mary Pope (New York : Scholastic, 1998)
Their magic tree house takes Annie and Jack to Pompeii just as Vesuvius is about to erupt, and they must find a Roman scroll before everything is covered with burning ash.
Book Links (A.L.A.), March 2007
Accelerated Reader AR-ATOS
Reading Counts RC
Keywords: Time travel -- Fiction; Tree houses -- Fiction; Volcanoes -- Fiction; Vesuvius (Italy) -- Eruption, 70 -- Fiction; Pompeii (Extinct city) -- Fiction